Diseño de un banco de pruebas para la determinación de las pérdidas de carga con variación de temperatura en agua (2019)
This document contains the entire procedure to design the test bench to determine load losses due to the variation in temperature, starting from a contextualization on the origin of this type of test benches, to subsequently consult the progress at the level International and national. The next step is to divide the test bench into each of its sub-systems, and then divide it into each of the functions that it is expected that it will be able to perform to fulfill the purpose for which it was designed, after performing This division for each of the different functions considers the different alternatives, to finally make the selection of the best alternative through the PUGH matrix, also in this section the initial design parameters are established.